Lifetime Number of Perpetrators and Victim–Offender Relationship Status Per U.S. Victim of Intimate Partner, Sexual Violence, or Stalking - Peterson, Cora; Liu, Yang; Merrick, Melissa; Basile, Kathleen C.; Simon, Thomas R. (Journal of interpersonal violence, 2021)
The aim of this study was to describe the U.S. population-level prevalence of multiple perpetrator types (intimate partner, acquaintance, stranger, person of authority, or family member) per victim and to describe the prevalence of victim–offender relationship status combinations. Authors analyzed U.S. nationally representative data from noninstitutionalized adult respondents with self-reported lifetime exposure to intimate partner violence, sexual violence, or stalking in the 2012 National Intimate Partner and Sexual Violence Survey (NISVS). An estimated 142 million U.S. adults had some lifetime exposure to intimate partner violence, sexual violence, or stalking. An estimated 55 million victims (39% of total victims) had more than one perpetrator type during their lifetimes. A significantly higher proportion of female victims reported more than one perpetrator type compared with male victims (49% vs. 27%). Among both female and male victims with >1 perpetrator type, the most prevalent victim–offender relationship status combinations all included an intimate partner perpetrator. Many victims of interpersonal violence are subject to multiple perpetrator types during their lifetimes. Prevention strategies that address polyvictimization and protect victims from additional perpetrators can have a substantial and beneficial societal impact. Research on victim experiences to inform prevention strategies is strengthened by comprehensively accounting for lifetime victimizations.